2022
DOI: 10.1155/2022/6476597
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Flowable Composite Resins on Periodontal Health, Cytokine Levels, and Immunoglobulins

Abstract: Objective. This study investigated the effects of flowable resin composites (FCR) on the restoration of noncarious cervical lesions (NCCL) and their impact on periodontal tissues. Materials and Methods. 30 periodontally healthy patients were assigned into three groups randomly; group VF: self-adhering FCR, group NF: fluoride-releasing FCR, and group SF: microhybrid FCR. Gingival crevicular fluid (GCF) volume levels of osteoprotegerin (OPG), immunoglobulins (IgA, IgM), and interleukins (IL-1, IL-1β, and IL-10) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…A recent study showed that fluoride-releasing flowable composite resins can initiate an inflammatory process when done as class v filling near the periodontium, as it increases gingivo clavicular fluid (GCF) and interleukin (IL) levels [26]. The characteristics of flowable composite as a cavity liner (marginal seal and reduced micro leakage at the gingival margin) are still under debate [27].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that fluoride-releasing flowable composite resins can initiate an inflammatory process when done as class v filling near the periodontium, as it increases gingivo clavicular fluid (GCF) and interleukin (IL) levels [26]. The characteristics of flowable composite as a cavity liner (marginal seal and reduced micro leakage at the gingival margin) are still under debate [27].…”
Section: Discussionmentioning
confidence: 99%
“…12,13,14 , electrolytes 9,15 , bacterial metabolic products 16 , host and bacterial enzymes, and enzyme inhibitors such as acid phosphatase, alkaline phosphatase 17 , cytokines 18,19,20 and immunoglobulins. 21,22 It has also been found that systemically administered drugs pass into the GCF. 23,24,25 Gingival Crevicular Fluid Collection Methods Three basic methods for obtaining GCF have been described 4 ;…”
Section: Introductionmentioning
confidence: 99%